Fast X‐ray Nanotomography with Sub‐10 nm Resolution as a Powerful Imaging Tool for Nanotechnology and Energy Storage Applications. Issue 21 (19th April 2021) - De Andrade, Vincent; Nikitin, Viktor; Wojcik, Michael; Deriy, Alex; Bean, Sunil; Shu, Deming; Mooney, Tim; Peterson, Kevin; Kc, Prabhat; Li, Kenan; Ali, Sajid; Fezzaa, Kamel; et al.
Abstract: In the last decade, transmission X‐ray microscopes (TXMs) have come into operation in most of the synchrotrons worldwide. They have proven to be outstanding tools for non‐invasive ex and in situ 3D characterization of materials at the nanoscale across varying range of scientific applications. However, their spatial resolution has not improved in many years, while newly developed functional materials and microdevices with enhanced performances exhibit nanostructures always finer. Here, optomechanical breakthroughs leading to fast 3D tomographic acquisitions (85 min) with sub‐10 nm spatial resolution, narrowing the gap between X‐ray and electron microscopy, are reported. These new achievements are first validated with 3D characterizations of nanolithography objects corresponding to ultrahigh‐aspect‐ratio hard X‐ray zone plates. Then, this powerful technique is used to investigate the morphology and conformality of nanometer‐thick film electrodes synthesized by atomic layer deposition and magnetron sputtering deposition methods on 3D silicon scaffolds for electrochemical energy storage applications. Abstract : Optomechanical breakthroughs in X‐ray nanotomography, leading to fast 3D tomographic acquisitions (85 min) with sub‐10 nm spatial resolution, are reported. These new achievements are first validated by 3D characterizations of novel X‐ray diffractive optics made by nanolithography and nanometer‐thick film electrodes synthesized by atomic layer deposition and magnetron sputtering deposition methods on 3D silicon scaffolds for electrochemical energy storage applications.